Understanding Stability and Change in Perceived Social Support in Parents of Autistic Children and Adolescents - Weiss, Jonathan A.; Robinson, Suzanne; Riddell, Rebecca Pillai; Flora, David (Frontiers in Rehabilitation Sciences, 2021)
Parents of children with autism often have their own support needs. Informal social support can be an important component of managing parenting-related stressors. We know very little about the factors that lead to higher levels of perceived social support or the potential reciprocal relationship social support has with other factors in parents of children with autism. The current longitudinal study examined the reciprocal relations of perceived social support and parent stress and child behavior problems across a one-year period, using three time points. There was remarkable stability in variables over time. Baseline perceived social support significantly predicted changes in child behavior and parent stress at the 6-month time point, but neither of those variables significantly predicted social support. This study adds to our understanding of social support and clarifies how perceived social support relates to other factors longitudinally.